Hypogonadism, Type-2 Diabetes Mellitus, and Bone Health: A Narrative Review - Russo, Vittoria; Chen, Rui; Armamento-Villareal, Reina (Frontiers in Endocrinology, 2021)
One of the complications from chronic hyperglycemia and insulin resistance due to type 2 diabetes mellitus (T2DM) on the hypothalamic-pituitary-gonadal axis in men is the high prevalence of hypogonadotropic hypogonadism (HH). Both T2DM and hypogonadism are associated with impaired bone health and increased fracture risk but whether the combination results in even worse bone disease than either one alone is not well-studied. It is possible that having both conditions predisposes men to an even greater risk for fracture than either one alone. Given the common occurrence of HH or hypogonadism in general in T2DM, a significant number of men could be at risk. To date, there is very little information on the bone health men with both hypogonadism and T2DM. Insulin resistance, which is the primary defect in T2DM, is associated with low testosterone (T) levels in men and may play a role in the bidirectional relationship between these two conditions, which together may portend a worse outcome for bone. The present manuscript aims to review the available evidences on the effect of the combination of hypogonadism and T2DM on bone health and metabolic profile, highlights the possible metabolic role of the skeleton, and examines the pathways involved in the interplay between bone, insulin resistance and gonadal steroids.